Impact of antithrombotic therapy on surgical treatment in patients with chronic subdural hematoma. (April 2020) - Amano, Toshiyuki; Matsuo, Satoshi; Miyamatsu, Yuichiro; Yamashita, Sojiro; Nakamizo, Akira
Highlights: Postoperative use of multiple antithrombotic agents can increase CSDH recurrence. CSDH recurrence within 2 weeks may be a predictor for the following reoperation. A longer cessation of antiplatelet agents can increase the risk of thromboembolism. Optimal timing for resumption of antithrombotic agents may be 3 days after surgery. Abstract: Objective: The effects of antithrombotic therapy on chronic subdural hematoma (CSDH) are controversial. Herein, we investigated the association of antithrombotic therapy with surgical complications and outcomes in patients with CSDH. Methods: We retrospectively analyzed 323 consecutive patients with CSDH who underwent single burr-hole craniostomy. Results: One hundred and eight patients (33%) underwent preoperative antithrombotic therapy. Hemorrhagic and thromboembolic complications were detected in 6 and 8 patients, respectively, which peaked at 3 and 4.5 days after CSDH surgery, respectively. CSDH recurrence was detected in 62 cases, and reoperation was required in 16 cases. Discontinuance of antiplatelet therapy for >2 weeks was significantly associated with thromboembolic complications (43%; p = 0.005). Postoperative use of multiple antithrombotic agents was significantly associated with CSDH recurrence (40%; p = 0.03). Further, earlier recurrence within 2 weeks was significantly associated with the following reoperation (62%; p = 0.006). Conclusions: To reduce morbidity and minimize the risk of CSDH reoperation, the optimal timing for resumption of antithrombotic agents is approximately 3 days after CSDH surgery. Postoperative use of multiple antithrombotic agents can increase CSDH recurrence, while earlier recurrence may be a predictor for the following reoperation.